The Maid of Orleans: A Tragedy - Schiller, Friedrich, 1759-1805; Swanwick, Anna, 1813-1899 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Maid of Orleans: A Tragedy" by Friedrich Schiller is a tragedy premiered in 1801. The play follows Joan of Arc through five acts, loosely depicting her mission to save France. While initially adhering to historical events, the plot takes dramatic liberties as Joan experiences an unexpected moment of weakness during battle, faces public accusations of sorcery, and ultimately confronts the consequences of her choices. This imaginative retelling became one of Schiller's most popular works during his lifetime. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Maid_of_Orleans_(play)
Release date is 2004-12-08
Produced by Tapio Riikonen and David Widger
Keywords: Tragedies (Drama); Joan, of Arc, Saint, 1412-1431 -- Drama; France -- History -- Charles VII, 1422-1461 -- Drama